Perceived Effect of Virtual Reality Headset on Students’ Dancing Performance - Amil, Centhony; Ompoc, Harlyn Mae; Valencia, Rimarc (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
This study aims to examine the student’s perception on the appropriateness of virtual reality headset as an aid in learning and performing dance. A descriptive-correlational type of research was employed. Sixty Physical Education students were chosen as respondents of the study. They were asked to wear a 3D Virtual Reality Box for an average of one minute. Inside it was a mobile phone with a dance video. A self-made questionnaire was then given for them to response. It is a likert scale that contains a series of statements on the appropriateness of the tool, inviting the respondents to respond to each based on how strongly they feel on each statement. The results shows that age, familiarity on the use of VR and the rate on the appropriateness of VR use is significantly correlated with the perception on the use of virtual reality on dancing performance. This implies that the more familiar and aware the respondents are with VR, the more they perceived that this is an appropriate tool in performing dance better. Furthermore, those who believe that virtual reality headset is appropriate as a learning tool in dancing also has a higher perception on the efficacy of VR headset on students’ dancing performance. This result suggests that teachers in physical education may consider using the virtual reality headset as a tool in teaching dance.